Analysis of Asymmetries in Foreign Trade Statistics - Kindl, Ondřej; Musil, Petr; Sixta, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
From January 2022 the EU member states have begun sharing their nationally collected micro-data with the aim of reducing asymmetries that stem from discrepancies in the international trade of goods. There are many reasons behind these discrepancies, such as differences in dates of departure and arrival, errors, or methodological requirements. In this thesis, I first begin with an introduction of the known reasons for asymmetries in foreign trade. In the next chapter a broad look at the situation among the European member states outlines the severity of the asymmetry phenomena in the European Union. Then, I introduce the micro-data exchange program, and how it works before diving deep into the Czech import micro-data with my custom solution for analyzing the data. I find and describe the largest asymmetries in terms of value by country, commodity, and reporting entity. I finish by recommending few improvements to the micro-data exchange program.
Vedoucí práce: Petr Musil
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses